Researching the transnational higher education policy landscape: Exploring network power and dissensus in a globalizing system (UCL Press, 2016)
This article reviews research on transnational higher education (TNHE) published in academic journals between 2006 and 2014 through the lenses of network power and dissensus. Conclusions suggest the need for more research on the 'entrapping' aspects of global social relations to provide a counterweight to the influence of dominant paradigms. It is argued that research at local-institutional level, harnessing the dissensus of the academic community with the needs and aspirations of students, provides the means to develop global imaginaries and initiate new policy directions that break free of entrapment and address the perverse outcomes of globalized knowledge-based economy models in higher education (HE).